A comparative analysis of in vitro growth inhibition of waterborne bacteria with bioactive plant Lippia nodiflora L. and camphor. Issue 54 (19th November 2016) - Pandey, Madhu; Pandey, Anand; Shukla, Shashi Kant; Kumar, Rajesh; Pathak, Ashutosh; Mishra, Rohit Kumar; Dikshit, Anupam
Abstract: In the current scenario, due to global deterioration of the environment and climate change, among them water pollution possesses serious threat to most of the populace. Waterborne pathogenic bacteria like Escherichia coli, Vibrio cholerae, Salmonella typhimurium, Klebsiella pneumoniae, etc. are responsible for several diseases such as diarrhoea, cholera, salmonellosis, etc. In order to overcome these waterborne bacterial diseases and for purification of water, plants have been of great use for their potential role from very ancient times. The present study deals with the Clinical & Laboratory Standards Institute (CLSI)-recommended broth microdilution antibacterial susceptibility assay of waterborne bacterial pathogens against Lippia nodiflora L. petroleum ether (LNPE) and ethanolic extracts (LNEE) prepared from the leaves and flowers together of Lippia nodiflora (Verbenaceae), in comparison to camphor. Growth inhibition of tested bacterial pathogens was recorded in from of IC50 and MIC values were found to be 0.171, 0.327 (mg/ml) against E. coli and V. cholerae, respectively, for LNPE extract. Thus, LNPE justifies its potential in inhibiting the growth of tested waterborne bacterial pathogens and creates an interest in further testing its active fraction for in vivo trials and organoleptic analysis; making it a good herbal replacement for the conventional water treatment.